Theory into practice, practice to theory: Action research in method development - Eden, C.; Ackermann, Fran (Elsevier BV * North-Holland, 2018)
The purpose of this paper is threefold. Firstly, although there have been many articles and books describing the nature of Action Research there are few examples of doing it in practice. We describe how a Research Oriented Action Research programme unfolded over many years focussing on the operationalisation of theory alongside the development of a soft-OR methodology. An outcome of this programme was the refinement of an Action Research method. Secondly, we present the development of an understanding of emergent strategy – a ‘theory’ that attracted both the researchers and managers in a number of organisations as one that could enhance the development of a soft-OR method and aid the process of strategy making. In doing so we demonstrate how research can be both rigorous and relevant. We also developed our understanding of emergent strategy in a manner that enables it to be used in practice. And thirdly, we show how the soft-OR method of Strategic Options Development and Analysis (SODA) methodology gradually became a strategy making methodology (Journey Making). Although much has been written describing the background to these soft-OR methodologies, this paper shows how and why they developed. We illustrate how relevant theory from a range of disciplines can inform practice, and how the process of implementing theory into method develops theory.